Frontalis sling operation using silicone rod for the correction of ptosis in chronic progressive external ophthalmoplegia. Issue 12 (11th September 2008) - Ahn, J; Kim, N J; Choung, H K; Hwang, S W; Sung, M; Lee, M J; Khwarg, S I
Abstract : Aims: The aim of the study was to evaluate the results of the frontalis sling operation using silicone rod for the correction of ptosis in chronic progressive external ophthalmoplegia patients. Methods: Chronic progressive external ophthalmoplegia patients who received the frontalis sling operation using silicone rods from 1999 to 2006 were included in this study. The medical records were retrospectively reviewed and the clinical characteristics and postoperative surgical results of these patients were analysed. This study was a retrospective, non-randomised, interventional case series and the main outcome measures were margin reflex distance, eyelid contour and corneal status. Results: Seven patients were recruited (one male and six female). The mean age at the time of operation was 29.6 (range 15–62) years. Two patients had unilateral ptosis and five patients had bilateral ptosis. The mean follow-up period was 22.7 (range 1–61) months. Satisfactory lid height was achieved in all patients. Although corneal erosions were detected in five patients 1 month after surgery, these findings eventually resolved in three patients 2 months later, after the use of artificial tear eyedrops and ointments. Conclusion: The frontalis sling operation using silicone rod can safely and effectively correct ptosis in chronic progressive external ophthalmoplegia patients without serious corneal complications.